Genômica de populações e genética geográfica de bovinos Pantaneiros e Curraleiro Pé-Duro com uso de polimorfismos de base única (SNP) - Silva, Marcelo Corrêa da (2015)
Livestock production has played a major role in social-economic aspects of rural development worldwide. In South America the introduction of domestic breeds such as cows, sheep and goats occurred during Spanish and Portuguese colonization expeditions over five hundred years ago. The Pantaneiro and Curraleiro Pé-Duro cattle breeds originate from this exact context and resemble historic, cultural and ecological aspects of traditional cattle farming in Brazil. This is characterized by rough and extensive breeding systems placed in many ecosystems of this country. Small population sizes and severe loss of genetic diversity in livestock breeds are of great concern regarding the scenario of global warming, emphasis on the sustainability of farming activities, the need of alternatives to attend market trends and promote rural development in a local perspective. This study was undertaken to explore patterns of genetic diversity in Pantaneiro e Curraleiro Pé-Duro cattle, aiming to identify differences between groups reared in several regions of Central-West, Central, North and Northeast of Brazil. Animals were genotyped using a SNP (single nucleotide polymorphism) chip containing over fifty thousand markers. Different analytical procedures were carried out using differentiation index, estimates of common ancestry, simple and multivariate clustering, inbreeding coefficients, genetic and also geographical distances. Spatial analysis was developed to allow the identification of patterns of genetic variation, specific geographical regions and herds of greater genetic differentiation. The results furnish insights in order to develop strategies to preserve genetic variability in Pantaneiro and Curraleiro Pé-Duro cattle.